2023
DOI: 10.1002/fee.2603
|View full text |Cite
|
Sign up to set email alerts
|

Responsibility, equity, justice, and inclusion in dynamic human–wildlife interactions

Abstract: In an era of rapid environmental change, human–wildlife interactions (HWIs) are increasingly complex and pervasive across ecosystems. Negative outcomes from such interactions continue to warrant much attention, given their implications for conservation and human livelihoods. However, framing HWIs solely along a coexistence–conflict continuum is overly simplistic because coexistence is not devoid of conflict and negates the temporal dynamics of potential outcomes. Furthermore, without thorough consideration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Human–wildlife conflicts may become amplified as both compete over limited resources in shared landscapes with ineffective mitigation strategies (Abrahms et al, 2023; Harris et al, 2023) (Box 2). In Kenya, livestock depredation events were highest when natural prey density was lowest during the wet season (Mukeka et al, 2019).…”
Section: Behavioral Pathways Of Global Changes Affecting Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Human–wildlife conflicts may become amplified as both compete over limited resources in shared landscapes with ineffective mitigation strategies (Abrahms et al, 2023; Harris et al, 2023) (Box 2). In Kenya, livestock depredation events were highest when natural prey density was lowest during the wet season (Mukeka et al, 2019).…”
Section: Behavioral Pathways Of Global Changes Affecting Dietmentioning
confidence: 99%
“…Human-wildlife conflicts may become amplified as both compete over limited resources in shared landscapes with ineffective mitigation strategies (Abrahms et al, 2023;Harris et al, 2023)…”
Section: B Ehavior Al Pathways Of G Lobal Chang E S Affec Ting Die Tmentioning
confidence: 99%
“…With increasing human populations, deteriorating habitats, globalization, and climate change, human‐wildlife interactions are becoming increasingly complex (Abrahms et al, 2023; Dietsch et al, 2016; Harris et al, 2023; Manfredo et al, 2020; Stinchcomb et al, 2022a). Research has shown that human‐wildlife interactions are shaped by various social factors and that human‐wildlife conflicts “are often manifestations of underlying human‐human conflicts” (Dickman, 2010, p. 458).…”
Section: Introductionmentioning
confidence: 99%
“…Wildlife agencies and organizations across the globe, including in North America, are striving to incorporate more diverse social values and perspectives into management planning (AFWA & WMI, 2019; Hodgson et al, 2020; König et al, 2021). Scholars have proposed the integration of responsibility, equity, justice, and inclusion as governing principles for human‐wildlife interactions (Harris et al, 2023). Specifically, addressing the needs of all possible ‘beneficiaries’ of wildlife remains an important aspect of good wildlife governance (Decker et al, 2016; Hare et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Animals attack crops, undoubtedly led by a preference for different parts of these plants, caused by the way crop losses. Given the recurrence of such losses at the periphery of various forests in Ivory Coast, our study has thus chosen to characterize patterns of crop raiding at the periphery of DCF and FMTE for a better understanding of why certain scientists reveal that wildlife losses cause crops are sometimes dramatic (FAO, 2010;Braczkowski et al, 2023;Nyeema et al, 2023). The specific objectives were to determine animal species involved by crops and their preference and evaluate the extent of losses caused by wildlife.…”
Section: Introductionmentioning
confidence: 99%